Uncovering the feasibility of using live Chlorella microbiomes in domestic and industrial wastewater treatment: insights into monoculture and synergistic mixed co-cultured system - Adhithya, S.; Nithya, Kamaraj; Sathish, Asha; Kumar, Vinod (Elsevier, 2025)
In recent years, numerous innovative technologies have emerged for algal bioremediation aimed at achieving clean water. Given the diverse functionalities of algae, algal bioremediation presents a viable alternative to conventional wastewater treatment systems. This study specifically emphasizes the use of Chlorella-based algal remediation when integrated with other microbial cultures for clean water applications. Our research provides a thematic review of the real-time integration of Chlorella and its co-cultures with other heterotrophic microbes in the treatment of domestic and industrial wastewater. While many review articles discuss the role of various microalgae species in wastewater treatment generally, to the best of our knowledge, no comprehensive review has documented the use of live algal systems, specifically focusing on a consortium of Chlorella algae, Chlorella bacteria, and Chlorella fungi for pollutant removal in wastewater treatment. This review primarily investigates the mechanisms by which live algal cell consortia—both single cultures and co-cultures—remove biochemical oxygen demand (BOD), chemical oxygen demand (COD), nitrogen, phosphorus, and heavy metals from wastewater. Additionally, the review addresses important observations concerning the characteristics of consortia, optimal growth conditions, the interactions between algae and contaminants, and the use of molecular diagnostic techniques such as PCR, FISH, and metagenomics. Our findings indicate that heterotrophic systems consisting of Chlorella and bacteria demonstrate higher treatment efficacy compared to systems made up of Chlorella and fungi.
Keywords: 4004 Chemical Engineering; 40 Engineering; 4011 Environmental Engineering; 6 Clean Water and Sanitation; Polymers; 34 Chemical sciences